Automation-Testing For Monitoring The Network Health Of Manufacturing Web-Based Application - Ayop, Zakiah; Mustafa, Nuridawati; Chang, Jonathan; Wong, Boon Min; Zainal Abidin, Zaheera; Lim, Jie hui; Anawar, Syarulnaziah (2014)
In this research, automation-testing approach is proposed to monitor the manufacturing web-based health application. Current monitoring system indicates that all components such as servers, applications, services, ports and URLs are not in critical condition, but operator on the production site could not operate the manufacturing application. The proposed approach will monitor the standard operation in manufacturing web-based application and determine the health state of the whole production. Automated script is executed and response time is captured as the performance indicator. A web-based reporting will display response times mapped in different graphs. From the preliminary testing result, graphs are compared and analyze. Finally, the comparison result will determine the abnormalities of the manufacturing application.